Neuroprotective Effects and Treatment Potential of Incretin Mimetics in a Murine Model of Mild Traumatic Brain Injury - Bader, Miaad; Li, Yazhou; Tweedie, David; Shlobin, Nathan A.; Bernstein, Adi; Rubovitch, Vardit; Tovar-y-Romo, Luis B.; DiMarchi, Richard D.; Hoffer, Barry J.; Greig, Nigel H.; Pick, Chaim G. (Frontiers in Cell and Developmental Biology, 2020)
Traumatic brain injury (TBI) is a commonly occurring injury in sports, victims of motor vehicle accidents, and falls. TBI has become a pressing public health concern with no specific therapeutic treatment. Mild TBI (mTBI), which accounts for approximately 90% of all TBI cases, may frequently lead to long-lasting cognitive, behavioral and emotional impairments. The incretins glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) are gastrointestinal hormones that induce glucose-dependent insulin secretion, promote β-cell proliferation and enhance resistance to apoptosis. GLP-1 mimetics are marketed as treatments for type 2 Diabetes Mellitus and are well tolerated. Both GLP-1 and GIP mimetics have shown neuroprotective properties in animal models of Parkinson's and Alzheimer's disease. The aim of this study is to evaluate the potential neuroprotective effects of liraglutide, a GLP-1 analogue, and twincretin, a dual GLP-1R/GIPR agonist, in a murine mTBI model. First, we subjected mice to mTBI using a weight-drop device and, thereafter, administered liraglutide or twincretin as a 7-day regimen of subcutaneous injections. We then investigated the effects of these drugs on mTBI-induced cognitive impairments, neurodegeneration and neuroinflammation. Finally, we assessed their effects on neuroprotective proteins expression that are downstream to GLP-1R/GIPR activation; specifically, PI3K and PKA phosphorylation. Both drugs ameliorated mTBI-induced cognitive impairments evaluated by the novel object recognition and the Y-maze paradigms in which neither anxiety nor locomotor activity were confounds, as the latter were unaffected by either mTBI or drugs. Additionally, both drugs significantly mitigated mTBI-induced neurodegeneration and neuroinflammation, as quantified by immunohistochemical staining with Fluoro-Jade/anti-NeuN and anti-Iba-1 antibodies, respectively. mTBI challenge significantly decreased PKA phosphorylation levels in ipsilateral cortex, which was mitigated by both drugs. However, PI3K phosphorylation was not affected by mTBI. These findings offer a new potential therapeutic approach to treat mTBI, and support further investigation of the neuroprotective effects and mechanism of action of incretin-based therapies for neurological disorders.